Digital transformation and global society. third International Conference, DTGS 2018, St. Petersburg, Russia, May 30-June 2, 2018, Revised selected papers /: third International Conference, DTGS 2018, St. Petersburg, Russia, May 30-June 2, 2018, Revised selected papers. Part II : (2018) - Unknown
No abstract available